Periprosthetic Joint Infection Prophylaxis in the Elderly after Hip Hemiarthroplasty in Proximal Femur Fractures: Insights and Challenges - Dolors Rodríguez-Pardo; Laura Escolà-Vergé; Júlia Sellarès-Nadal; Pablo S. Corona; Benito Almirante; Carles Pigrau (MDPI AG, 2021)
We review antibiotic and other prophylactic measures to prevent periprosthetic joint infection (PJI) after hip hemiarthroplasty (HHA) surgery in proximal femoral fractures (PFFs). In the absence of specific guidelines, those applied to these individuals are general prophylaxis guidelines. Cefazolin is the most widely used agent and is replaced by clindamycin or a glycopeptide in beta-lactam allergies. A personalized antibiotic scheme may be considered when colonization by a multidrug-resistant microorganism (MDRO) is suspected. Particularly in methicillin-resistant Staphylococcus aureus (MRSA) colonization or a high prevalence of MRSA-caused PJIs a glycopeptide with cefazolin is recommended. Strategies such as cutaneous decolonization of MDROs, mainly MRSA, or preoperative asymptomatic bacteriuria treatment have also been addressed with debatable results. Some areas of research are early detection protocols in MDRO colonizations by polymerase-chain-reaction (PCR), the use of alternative antimicrobial prophylaxis, and antibiotic-impregnated bone cement in HHA. Given that published evidence addressing PJI prophylactic strategies in PFFs requiring HHA is scarce, PJIs can be reduced by combining different prevention strategies after identifying individuals who will benefit from personalized prophylaxis.